2002
DOI: 10.1017/s1068280500004032
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Farm Management and Long-Term Farm Financial Performance

Abstract: The financial performance and relationships between several management factors and financial performance are examined in a panel of 107 New York dairy farms. A panel regression model with fixed effects is estimated in an effort to identify management factors that influence profitability. The model is estimated with two-stage least squares to account for endogenous farm size and debt use variables. Production management factors such as farm size, rate of milk production, and milking system had a positive impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 20 publications
6
78
0
5
Order By: Relevance
“…El-Osta and Johnson (1998), El-Osta and Morehart (2000), Short (2000) and Gloy et al (2002) used dairy herd size as a measure of dairy farm size. For the purposes of this study, the natural logarithm of dairy herd size, LNCOWS it , was used.…”
Section: +/-mentioning
confidence: 99%
See 4 more Smart Citations
“…El-Osta and Johnson (1998), El-Osta and Morehart (2000), Short (2000) and Gloy et al (2002) used dairy herd size as a measure of dairy farm size. For the purposes of this study, the natural logarithm of dairy herd size, LNCOWS it , was used.…”
Section: +/-mentioning
confidence: 99%
“…El-Osta and Johnson (1998), Short (2000) and Gloy et al (2002) found that milking rate (production per cow) is related positively to farm profitability. According to Gloy et al (2002), milking rate is assumed to contain latent characteristics of the milk producer's knowledge, experience, husbandry policy and feeding practices.…”
Section: +/-mentioning
confidence: 99%
See 3 more Smart Citations